2020
DOI: 10.1108/bepam-12-2018-0159
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of stakeholders' willingness to adopt construction 4.0 technologies for construction projects

Abstract: PurposeConstruction 4.0 technology has the capabilities for improving the design, management, operations and decision making of construction projects. Therefore, this study aimed at examining the willingness of construction professionals towards adopting construction 4.0 technologies.Design/methodology/approachThe study adopts a survey design, and construction professionals in South Africa are assessed using a convenience sampling technique through a structured questionnaire. The questionnaire was analysed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 63 publications
7
61
0
2
Order By: Relevance
“…(Thomas, 2019) as well as drones, radio-frequency identification (RFID), wireless sensors etc. (Osunsanmi et al, 2020). (Osunsanmi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…(Thomas, 2019) as well as drones, radio-frequency identification (RFID), wireless sensors etc. (Osunsanmi et al, 2020). (Osunsanmi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As Industry 4.0 is driving an incremental shift in paradigms, there arises a challenge for researchers to understand how appropriate technologies can be assembled to assist in achieving the goals of construction businesses (Dowd and Marsh, 2020) . Osunsanmi et al (2020) categorised the Industry 4.0 technologies in relevance to their functionalitytechnologies supporting smart construction sites, simulation and visualisation. They concluded that even though there maybe willingness among construction professionals to adopt these technologies, the possibility to fully integrate them was low predominantly due to lack of technical know-how, low investment to research, lack of buy-in from clients and lack of performance or regulatory standards.…”
Section: Introductionmentioning
confidence: 99%
“…Craveiro et al (2019) and Tahmasebinia et al (2020) focus on additive manufacturing and 3D printing as an enabling technology for Industry 4.0 integration in the construction industry. Thus, current research in the built environment is limited to exploring the exponential technological prowess of Industry 4.0, with very little work on its implications to the construction business model, strategy and competitive advantage (Osunsanmi et al, 2020;Craveiro et al, 2019;Tahmasebinia et al, 2020;Patrucco et al, 2020;Oesterreich and Teuteberg, 2016;Newman et al, 2020;You and Feng, 2020;Munoz-La Rivera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…About 40% of the respondents agree that improved skills and expertise, as well as the impact of new digital technologies, are the most significant factors in maintaining a competitive advantage in the construction sector. Osunsanmi et al (2020), in their study of stakeholders' willingness to adopt Construction 4.0 technologies, have identified key areas and barriers for wider digitalisation and technology usage in the construction industry (see Table 1). Other studies in this area have been provided by the National Federation of Builders of Great Britain (2015) among 1,200 companies and by the UK's National Building Specification (2018) among 808 companies.…”
Section: Construction Sector and Automotive Industry In The Context Of Digitalisationmentioning
confidence: 99%